Preparation of Specimen for Transmission Electron Microscopy using Freeze Substitution and Agitation - Grahammer, Johannes (Jihočeská univerzita, 2018)
The quality of biological samples for Transmission Electron Microscopy prepared using High Pressure Freezing and Freeze Substitution with a novel agitation module invented by Helmuth Goldhammer and Siegfried Reipert was compared to Cells prepared without agitation and the Freeze Substitution protocol by Obornik et al. The amount of extraction was quantified via immunolabelling of RuBisCO inside the plastids of the Alveolate Chromera Velia Mechanical Damages were quantified by counting of obviously damaged and intact cells at low magnification
Preparation of Specimen for Transmission Electron Microscopy using Freeze Substitution and Agitation
-
Keywords: Freeze Substitution; High Pressure Freezing; Agitation; Immunolabeling; RuBisCO; Freeze Substitution; High Pressure Freezing; Agitation; Immunolabeling; RuBisCO